The Application of Voice Search Technology in Online Sports Product Sales Systems - Kaewchada, Sopee; Kidjaideaw, Sunisa; Rattaphun, Munlika; Kaykaew, Worapot (KKU Science Journal, 2025)
This research aims to 1) study the process of voice-based product search, 2) develop an online sports product sales system using voice search technology, and 3) evaluate user satisfaction with the developed system. The system development followed the Unified Process methodology, utilizing the Unified Modeling Language (UML) for model representation. A client/server web application was built with PHP and MySQL, using Full-text Search to retrieve relevant information. The sample group consisted of 35 participants, including loyal customers, employees, and system administrators. The research findings were as follows: 1) The study of the voice-based product search process revealed that it begins with capturing the user’s voice, converting it into text, and then using the text for information retrieval. 2) The developed online sports product sales system integrated with voice search technology consists of five subsystems: user verification, product management, voice search, ordering, and order reports. 3) The user satisfaction study found that satisfaction with the system was high, with an average score of 4.51.